Michel Foucault: um itinerário analítico acerca da atitude crítica - Silva, Alexandre dos Santos (2012)
The presente work is aimed at the analysis of the analytical itinerary of the notion of critical atitude in Michel Foucault. For that, we attempt to evaluate the types of power configuration, according to the thinker, attempting, above all, to the constitution of pastoral power as a practise of ruling the souls . According to Foucault, one can track the passage of the souls‟s pastoral to the political domination of men, named by the philosopher as governmentality , or the art of governing. Remarkably approached in the 1978 course, Security, Territory, Population , the theme of the political governamentality will give to Foucault the opportunity to introduce the issue of counter-conduct to the practices of men government, or even better, critical attitude. Therewith, this research has as its kernel to scavenge the analytical path of the critical attitude‟s notion in Michel Foucault. This will be done trying to piece the foucaultian theorical itinerary in relation to the power variations. In this sense, the study of the lecture Qu est-ce la Critique and of the 1978 course constitutes the primary writings to be considerated in this work